Evaluating the alignment between needs and the availability of physical education, sports, and health facilities - Rifky Abrori; Sudarwan Danim; Azizatul Khairi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study examines the alignment between ideal needs and the actual availability of Physical Education, Sports, and Health (PESH) facilities at the secondary school level. Adequate PESH facilities are essential to support safe, effective, and student-centered learning; however, many schools, particularly in resource-limited contexts, face persistent infrastructural constraints. The urgency of this research lies in the need to move beyond descriptive assessments of facility availability toward an evaluative understanding of gaps and policy responses. The study aims to identify the ideal PESH facility needs, assess actual facility conditions, analyze discrepancies between standards and practice, and examine school-level policies to address these gaps. A qualitative descriptive approach was employed using the Discrepancy Evaluation Model (DEM). The research population consisted of school leaders, PESH teachers, and facility management staff, with participants selected through purposive sampling based on their roles and involvement in facility management. Data were collected through observations, interviews, and document analysis. The findings reveal low to moderate alignment between ideal standards and actual provision, with significant gaps in facility quantity, quality, supporting infrastructure, and maintenance systems. Despite these limitations, PESH learning continues through adaptive instructional strategies and collaboration with external stakeholders. The study recommends strengthening needs-based facility planning, establishing systematic maintenance procedures, and developing specific school-level policies to support sustainable PESH facility development. The study concludes that improving PESH learning quality requires systematic facility planning and targeted policy frameworks to progressively reduce discrepancies and ensure sustainable educational development.